2006
DOI: 10.2337/diacare.29.01.06.dc05-1617
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Asymptomatic Peripheral Artery Disease in Subjects Over 60 Years of Age

Abstract: T he ankle-brachial index (ABI) is a noninvasive, low-cost, and useful test for detecting asymptomatic peripheral artery disease (PAD). An ABI Ͻ0.9 has a sensitivity of 95% and a specificity of 99% in identifying PAD when compared with arteriography (1). A low ABI predicts risk of cardiovascular death, myocardial infarction, PAD events, and stroke (2,3). Although an elevated prevalence of a low ABI has been described in subjects with metabolic syndrome and a history of cardiovascular disease (4), there is no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…Even after the exclusion of subjects with diabetes, there were graded increases in PAD prevalence with increasing HOMA-IR quartiles, although the associations between HOMA-IR and PAD were no longer statistically significant. Our data support prior observations that PAD is associated with the metabolic syndrome 11,12,36 and glucose intolerance, 13 both surrogate markers of insulin resistance. In contrast to the limited data on the association of insulin resistance and PAD, the link between inflammation and PAD has been well established.…”
Section: Discussionsupporting
confidence: 81%
“…Even after the exclusion of subjects with diabetes, there were graded increases in PAD prevalence with increasing HOMA-IR quartiles, although the associations between HOMA-IR and PAD were no longer statistically significant. Our data support prior observations that PAD is associated with the metabolic syndrome 11,12,36 and glucose intolerance, 13 both surrogate markers of insulin resistance. In contrast to the limited data on the association of insulin resistance and PAD, the link between inflammation and PAD has been well established.…”
Section: Discussionsupporting
confidence: 81%
“…Much less information is available on the relationship between the MetS and incident lower extremity peripheral artery disease (PAD) with most data deriving from cross-sectional reports710. One of two previously published prospective evaluations suggested that the MetS is a predictor of end-stage PAD (lower extremity amputation or revascularization), but that this risk increase is largely attributable to the impact of diabetes alone11.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that MetS is associated with cardiovascular diseases such as coronary heart disease (CHD) and peripheral vascular disease [2][3][4]. However, few studies have examined the association of this syndrome with electrocardiographic subclinical risk factors such as a long corrected QT interval (QTc) [5].…”
Section: Introductionmentioning
confidence: 99%